Post-transcriptional regulation of gene expression by mitogen-activated protein kinase p38. - Clark, A; Dean, J; Saklatvala, J (2003)
The mitogen-activated protein kinase p38 pathway was originally identified as a signalling cascade activated by pro-inflammatory stimuli and cellular stresses, and playing a critical role in the translational regulation of pro-inflammatory cytokine synthesis. In almost a decade since this discovery, a great deal has been learned about the role of the p38 pathway in the post-transcriptional regulation of pro-inflammatory gene expression. However, important questions remain to be answered concerning the specificity and mechanism or mechanisms of action of p38. This review describes recent progress and remaining puzzles in the field of post-transcriptional regulation by p38.